Influence of dialect use on speech perception: a mismatch negativity study. Issue 6 (3rd July 2017) - Bühler, Jessica C.; Schmid, Stephan; Maurer, Urs
ABSTRACT: Using an electroencephalography (EEG)-based mismatch negativity (MMN) paradigm, we investigated whether higher familiarity with a dialectal variety of German (Swiss German (CHG) vs. Standard German (StG)) impacted speech perception at the neural and the behavioural level. Specifically, we examined 30 CHG- and StG-native adults, by contrasting a pseudoword containing an allophonic phoneme variant found in both dialects (i.e. standard) with 2 deviant stimuli encompassing allophonic phoneme variants, of which one was more familiar for CHG natives and the other was more familiar for StG natives. The same stimuli were used in a behavioural "same–different" discrimination task. Behavioural pseudoword differentiation was better for more familiar allophonic phoneme variants. MMN measures revealed significant fronto-central and temporal deviance-by-language-group interactions, primarily driven by larger MMN responses for less familiar deviants in StG natives. We conclude that a higher degree of familiarity with allophonic variants seems to impact neural processing efficiency, to the extent that less familiar variants demand more wide-spread activation processes.